Retagging identifies dendritic cell-specific intercellular adhesion molecule-3 (ICAM3)-grabbing non-integrin (DC-SIGN) protein as a novel receptor for a major allergen from house dust mite - Emara, Mohamed; Royer, Pierre-Joseph; Mahdavi, Jafar; Shakib, Farouk; Ghaemmaghami, Amir M. (American Society for Biochemistry and Molecular Biology, 2012)
Dendritic cells (DCs) have been shown to play a key role in the initiation and maintenance of immune responses to microbial pathogens as well as to allergens, but the exact mechanisms of their involvement in allergic responses and Th2 cell differentiation have remained elusive. Using retagging, we identified DCSIGN as a novel receptor involved in the initial recognition and uptake of the major house dust mite and dog allergens Der p 1 and Can f 1, respectively. To confirm this, we used gene silencing to specifically inhibit DC-SIGN expression by DCs followed by allergen uptake studies. Binding and uptake of Der p 1 and Can f 1 allergens was assessed by ELISA and flow cytometry. Intriguingly, our data showed that silencing DC-SIGN on DCs promotes a Th2 phenotype in DC/T cell co-cultures. These findings should lead to better understanding of the molecular basis of allergen-induced Th2 cell polarization and in doing so paves the way for the rational design of novel intervention strategies by targeting allergen receptors on innate immune cells or their carbohydrate counterstructures on allergens.